Branding of Osing Traditional School in Banyuwangi through the Instagram account @pesinauan.osing - Khoir, Raihan Syairojil; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to preserve the culture in Osing traditional schools through the @pesinauan.osing Instagram account so that the community can know and preserve the tradition of local cultural wisdom. The presence of Instagram has a considerable influence as a medium for disseminating information that is not yet known to the audience. In this study, the indicator of the strength of brand association is strong with Osing traditional schools through typical images of Osing, stories about the daily life of the Osing traditional school community. In addition, this account also succeeded in creating a favorability of brand association which is proven by inspiring narratives and the use of attractive visuals. The uniqueness of this account lies in the collaboration between Osing traditional schools and local artists. All of this is in line with Keller's branding image theory, which emphasizes the importance of building strong, positive, and unique brand associations This research uses the basis of qualitative research methods based on the objects of study related to osing traditional schools. Researchers collect data and information by observing documents, observing behavior, and interviewing several informants. The results of this research can provide information to the audience through Instagram media and can increase the number of viewers on the @pesinauan.osing Instagram account through videos or photos that present the form of content selling ideas that carry the concept of preserving the tradition of local cultural wisdom of Osing Banyuwangi. Great benefits are brought up through Instagram media which can be evidenced by the increase in the number of viewers. The use of brand image that has been implemented can build a positive image in osing traditional schools starting from the use of logos, designs and colors. With this research, Instagram @pesinauan.osing can popularize and develop traditions that have been born since ancient times.